Analisis Strategi dan Peran PT Jasa Raharja JawaTimur sebagai Koordinator Program Mudik Gratis Tahun 2022 dalam Mengurangi Tingkat Kecelakaan Ditinjau dari Angka Pemberian Santunan Kecelakaan - Ramadanti, Firda Gangsar; Kamaliyah, Alfi; Madhiyah, Alfiyatul; Mafaza, Aunillah (Jurnal Manajemen dan Inovasi (MANOVA), 2023)
The free homecoming program is one of the annual programs that is eagerly awaited by people who want to experience homecoming but don't have extra costs. This activity is carried out in order to reduce the level of traffic accidents, especially motorcycle accidents and is a form of BUMN efforts to help the community reduce the economic burden in carrying out homecoming. The research method used is a qualitative approach with descriptive methods. Data collection techniques in this study are by observing, interviewing, and studying documentation. The results of this study indicate that the strategy and role of PT Jasa Raharja as the Coordinator of the 2022 Free Homecoming Program are (1) selection of EO (Event Organizer); (2) efforts to socialize the 2022 Safe Homecoming Program with SOEs; (3) guaranteeing the safety and health of travelers. And the role carried out by PT Jasa Raharja as coordinator of the 2022 Free Mudik Program is to organize and ensure that the Opening Ceremony activities run well for all contributing BUMN companies. Comparison of the incidence rate index and the provision of Free Homecoming Program compensation based on the last three periods 1) There is an increase in the number of incidents and the number of accident victims in 2022; 2) The amount of compensation given to accident victims during the 2022 Eid homecoming decreased compared to the 2019 Eid homecoming; and 3) The registration quota from year to year is uncertain and subject to change.